On multi-sector and multi-technique models, production functions and Goodwin cycles: a reply to Libman - Robert A. Blecker; Mark Setterfield (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
Emiliano Libman's constructive comments on our recent book, Heterodox Macroeconomics: Models of Demand, Distribution and Growth (HM), raise three main points of contention: the suitability of single-sector/single-technique (as opposed to multi-sector/multi-technique) models; the appropriate choice of production function; and the distinction between limit cycles and closed orbits as representations of Goodwinian dynamics. In this reply, we respond to Libman's critique in a manner that is designed to develop his arguments into a useful addendum to our book. In so doing, we hope that this exchange will engage interested students and other readers in issues and avenues of inquiry that lie beyond some of the first-pass simplifications in HM.
Keywords: E11; E12; O33; O41; B51; D24; 330; choice of technique; production functions; Goodwin cycles; multi-sectoral models; technological change; factor substitution